The relationship between vitamin E and C intake with total activity of erythrocytes and breast milk superoxide dismutase in lactating mothers - Ninik Mudjihartini; Diyah Eka Andayani; Sheira Taflah Putri Handana (Acta Biochimica Indonesiana)
Background: Human milk contains many components, one of them is superoxide dismutase (SOD). Vitamin E and C, together with SOD, can prevent oxidative stress.